Association of social support and antepartum depression among pregnant women - Friedman, Lauren E. (2020)
Background: : Few investigators have evaluated the association between early pregnancy social support and depression; however, increased social support may improve mental health during pregnancy. Our objective is to examine whether in early pregnancy there is an association between social support and maternal depression among women in Peru. Methods: : 2,062 pregnant women participated in structured interviews. Early pregnancy social support was measured using the Social Support Questionnaire (SSQ-6). We evaluated the number of individuals that participants could turn to in different situations (Social Support Number Score; SSQN) and their satisfaction with support received (Social Support Satisfaction Score; SSQS). Median SSQN and SSQS characterized participants according to high and low levels of support. SSQN family vs. non-family support were also evaluated separately. Antepartum depression was assessed using the Patient Health Questionnaire-9. Multivariable logistic regression procedures were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs). Results: : 39.6% of women reported high SSQN and 45.5% reported high SSQS. Approximately 25% had antepartum depression. Women with high SSQN had 22% lower odds of antepartum depression (OR = 0.78; 95%CI: 0.63–0.97). Similarly, women with high SSQS scores had 45% lower odds of antepartum depression (OR = 0.55; 95%CI: 0.45–0.68). Women with high SSQN non-family scores had 30% lower odds antepartum depression compared to those with low SSQN non-family scores (OR = 0.70; 95%CI: 0.57–0.86). The association between SSQN family scores and antepartum depression did not reach statistical significance. Conclusion: : Increased social support may improve maternal mental health during pregnancy and this association should be assessed in longitudinal studies.